Research on the coupled support technology of a composite rock beam-retained roadway roof under close coal seams - Li, Tingchun; Yang, Liu; Zhu, Qingwen; Liu, Daowei; Wang, Yichao (Frontiers in Ecology and Evolution, 2023)
Introduction The technology of gob-side entry retaining without coal pillars in close (distance) coal seams is still immature, and the roof control and support technology in this case is not perfect. Methods In this paper, the coupled support technology of a composite rock beam roof under close coal seams is systematically studied by using theoretical analysis, numerical simulation and field test. Results Both the floor slip calculation results and numerical simulations indicate that the vertical failure depth in the plastic zone of the #8 coal seam has not penetrated the roof of the #9 coal seam after mining, which is consistent with the field electronic imaging results. A theoretical formula for a composite rock beam model anchored by high-prestressed anchor cables was derived, and a formula for the optimal spacing of anchor cables under noncompressive shear failure of the roof was obtained. Identification of the internal stress hazard region of the rock beam provides a basis for determining the locations of vertical support. Through numerical simulation of different support schemes, including roof cutting, arrangement of high-prestressed anchor cables, and setting up of vertical supports, roof cutting was found to effectively reduce the stress of supporting structure and roof pressure. Setting up of vertical supports can reduce the roof convergence by 25.2%, and coupling with anchor cables can reduce the convergence by more than 49.1%. The feasibility of this support scheme was verified through field tests, with a maximum convergence of 99 mm between the roof and floor. Discussion This two-way verification approach, in which the damage degree of the roof of a close coal seam is analyzed through multiple means, targeted support plans are proposed, the support mechanisms are explored, and feedback is conducted through field tests, plays a certain guiding role in solving roof control of the gob-side entry retaining under similar geological conditions.